(untitled) (Baghdad Science Journal, 2024)
In this research work, a new type of concrete based on sulfur-melamine modification was introduced, and its various properties were studied. This new type of concrete was prepared based on the sulfur-melamine modification and various ingredients. The new sulfur-melamine modifier was fabricated, and its fabrication was confirmed by IR spectroscopy and TG analysis. The surface morphology resulted from this modifier was studied by SEM and EDS analysis. The components ratios in concrete, chemical and physical characteristics resulted from sulfur-melamine modifier, chemical and corrosion resistance of concrete, stability of concrete against water adsorption, stability of concrete against freezing, physical and mechanical properties and durability, modulus of elasticity, and thermal expansion coefficient of the studied sulfur concrete were investigated. The IR results confirmed the amino functional groups (attached melamine ring) and the formation of polymer sulfur chains. The sulfur-melamine modification thermic mass loss was one step. The mass loss processes of the modifier were endothermic processes. The obtained SEM results revealed that the sulfur-melamine modifier had a more porous structure, without any crystal forms. EDS analysis showed that the nitrogen atoms were accounted for 51.33% of total mass while the carbon was 30.94% of total mass. The stability of sulfur-melamine modifier-based concrete was very high in the various aggressive solutions. The low size of aggregates-based concrete had more density, i.e., 2417 kg3. The concrete density was decreased slowly with increase in the size of aggregate. The average deformation of studied concrete was (0.0030-0.0033), confirming that the deformation performance of concrete was better than the traditional concretes. The obtained results also confirmed that value of thermal expansion coefficient for sulfur-melamine modified concrete was 17.2×10-6\˚C.